Operationalizing resilience in Australian and New Zealand agroecosystems - Fletcher, Cameron S; Craig, Miller; Hilbert, David W (Proceedings of the 50th Annual Meeting of the ISSS - 2006, Sonoma, CA, USA, 2006)
We present techniques that we have developed to operationalize the concept of resilience, as promoted by The Resilience Alliance (www.resalliance.org). We also outline a new program of research applying these techniques across a diverse range of Australian and New Zealand systems to begin operationalizing resilience management wherever humans interact with the natural environment.Resilience is an emergent system-wide property that describes the capacity of a system to absorb perturbations and persist in a variable environment. In human-modified natural systems, such as agro-ecosystems and landscape mosaics containing both farmland and remnant native vegetation, we claim: a) that long-term system dynamics is determined by interactions and feedbacks between social, economic and ecological sub-systems, rather than instantaneous stocks and flows of material throughout a system; and b) that instantaneous system behaviour is often dominated by stochasticity, variability and uncertainty. We propose a new mathematical technique, based on dynamical systems theory and systems science, which embraces uncertainty using the concept of resilience. We hope that this approach will provide a useful complement to “precise” simulation models of agricultural systems.We examine these techniques in the context of a new research program studying resilience in Australian and New Zealand agro-ecosystems. This research program is allowing us to apply these techniques to a wide range of case studies, producing quantitative results that operationalize the concept of resilience at a scale not previously achieved.